Effect of temperature on the chromatographic retention of ionizable compounds: II. Acetonitrile–water mobile phases - Gagliardi, Leonardo Gabriel (2005)
The retentive behavior of weak acids and bases in reversed-phase liquid chromatography (RPLC) upon changes in column temperature has been theoretically and experimentally studied. The study focuses on examining the temperature dependence of the retention of various solutes at eluent pH close to their corresponding pKa values, and on the indirect role exerted by the buffer ionization equilibria on retention and selectivity. Retention factors of several ionizable compounds in a typical octadecylsilica column and using buffer solutions dissolved in 30% (v/v) acetonitrile as eluent at five temperatures in the range from 25 to 50 °C were carefully measured. Six buffer solutions were prepared from judiciously chosen conjugated pairs of different chemical nature. Their pKa values in this acetonitrile–water composition and within the range of 15–50 °C were determined potentiometrically. These compounds exhibit very different standard ionization enthalpies within this temperature range. Thus, whenever they are used to control mobile phase pH, the column temperature determines their final pH. Predictive equations of retention that take into account the temperature effect on both the transfer and the ionization processes are evaluated. This study demonstrates the significant role that the selected buffer would have on retention and selectivity in RPLC at temperatures higher than 25 °C, particularly for solutes that coelute.